Analisis Putusan Pengadilan Agama Sangatta Atas Perceraian Dengan Alasan Kelainan Seksual - Andryansyah Andryansyah; Musthato’ Musthato’; Anggra Prima (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
In Positive Law in Indonesia divorce is regulated in legislation, namely Law No. 16 of 2019 concerning marriage strengthened in Minister of Religion Regulation Number 30 of 2024 and the Compilation of Islamic Law (KHI). This study aims to understand the considerations of the Panel of Judges in deciding cases and the views of Islamic Law related to divorce on the grounds of sexual disorder in the Sangatta Religious Court. This research uses a Qualitative method Normative juridical approach in this research uses normative legal research methods, focusing on legal systematics. Data was collected through observation techniques, in-depth interviews with the Head of the Sangatta Religious Court and documentation from various related sources. The results showed that the Judge's consideration related to divorce on the grounds of sexual disorder did not focus on the sexual disorder but on other factors such as indecent acts in sex and non-fulfillment of rights and obligations in marriage also contributed to this case.